Cervical epidural anaesthesia for thyroid surgery - Khanna, R; Singh, DK (Kathmandu University Medical Journal, 2010)
Background: Cervical epidural anaesthesia is a regional anaesthesia technique which has been used for upper limb surgery, upper thoracic wall surgery, carotid artery surgery and neck dissections. Anaesthesia for thyroid surgery can be complicated due to the altered functional status of the thyroid or its large size. Objective: This prospective study was designed to assess the effectiveness and safety of cervical epidural anaesthesia for thyroid surgery. Materials and methods: Cervical epidural anaesthesia was attempted in 9 patients and the results compared with 44 patients who underwent thyroid surgery under conventional general anaesthesia with endotracheal intubation. The epidural catheter was placed in the C7 - T1 vertebral interspace and 10 - 15 ml of 1% Lignocaine with adrenaline was injected. Results: The technique of cervical epidural anaesthesia was successfully used in 8 out of 9 patients in whom it was attempted All patients were maintained in a state of conscious - sedation and effective analgesia was obtained in all 8 patients. There were no significant complications especially those related to diaphragmatic function and cardiovascular stability. In contrast patients undergoing surgery under conventional general anaesthesia had complications related to endotracheal intubation, cardiac arrhythmias and hypotension Conclusion: The technique of cervical epidural anaesthesia should be considered in thyroid patients where difficult endotracheal intubation is anticipated and in those in whom alterations in thyroid functional state make them vulnerable to cardiovascular complications under conventional general anaesthesia. Key words: thyroid surgery; cervical epidural anaesthesia DOI: 10.3126/kumj.v7i3.2731 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 242-245